Telescopic denture load distribution based on the telescopic crown design and material - Devina Angga; Ariyani; Haslinda Z. Tamin (Indonesian Journal of Prosthodontic, 2023)
Retentive force (RF) on the telescopic crown (TC) retainer will be distributed to the abutment teeth. The optimal load distribution measured by RF on the abutment is 5-9 N. If the force is applied excessively, it will damage the tooth's supporting tissue, causing periapical lesions, bone resorption, and mobility. However, if the RF is minimal, the dent-ure will not retentive. This paper will go through how RF will vary based on the chosen design and material. The cy-lindrical, conical, and resilient TC design are affected by the taper angle and the distance between the primary crown (PC) and secondary crown (SC). Resilience design can be modified by Marburg, Hofmann, and Yalisove. To create the precise taper angle and space in telescopic dentures (TD), CAD/CAM can now be used for the manufacture of TD using metal and non-metal materials. It is concluded that cylindrical TC design is rarely used because it is diffi-cult to get tight contact between PC and SC, therefore conus or resilience design is more recommended. The smal-ler the taper angle, the greater the RF, but this depends on the material used. While the space between PC and SC, which is less than 50 μm, can also affect RF